Comparison of Different algorithm for Speed Control of Brushless D.C Motor Using Matlab Simulink - Pinkey*, Rekha Rana* Gyanender Kumar** (International Journal of Scientific Research and Management (IJSRM), 2015)
Brushless DC Motors have a permanent magnet rotor and the stator winding are wound such that the backelectromotive force (EMF) is trapezoidal. The motor posses high Torque/weight ratio, operate at very high speed, verycompact & electronically controlled. In this paper, we have to use three algorithms ZN, GA & PSO respectively. Onthe basis of performance of these three techniques, PSO have high efficiency as compare to other two techniques Errorrate in PSO algorithm is 1.395 which is less than ZN algorithm & GA algorithm.